A survey of seizures and current treatments in 15q duplication syndrome. Issue 3 (6th February 2014) - Conant, Kerry D.; Finucane, Brenda; Cleary, Nicole; Martin, Ashley; Muss, Candace; Delany, Mary; Murphy, Erin K.; Rabe, Olivia; Luchsinger, Kadi; Spence, Sarah J.; Schanen, Carolyn; Devinsky, Orrin; et al.
Summary Objective Seizures are common in individuals with duplications of chromosome 15q11.2‐q13 (Dup15q). The goal of this study was to examine the phenotypes and treatments of seizures in Dup15q in a large population. Methods A detailed electronic survey was conducted through the Dup15q Alliance containing comprehensive questions regarding seizures and their treatments in Dup15q. Results There were 95 responses from Dup15q families. For the 83 with idic(15), 63% were reported to have seizures, of which 81% had multiple seizure types and 42% had infantile spasms. Other common seizure types were tonic–clonic, atonic, myoclonic, and focal. Only 3 of 12 individuals with int dup(15) had seizures. Broad spectrum antiepileptic drugs (AEDs) were the most effective medications, but carbamazepine and oxcarbazepine were also effective, although typical benzodiazepines were relatively ineffective. There was a 24% response rate (>90% seizure reduction) to the first AED tried. For those with infantile spasms, adrenocorticotropic hormone (ACTH) was more effective than vigabatrin. Significance This is the largest study assessing seizures in Duplication 15q syndrome, but because this was a questionnaire‐based study with a low return rate, it is susceptible to bias. Seizures are common in idic(15) and typically difficult to control, often presenting with infantile spasms and progressing to a Lennox‐Gastaut–type syndrome. Seizures in those with int dup(15) are less common, with a frequency similar to the general autism population. In addition to broad spectrum AED, medications such as carbamazepine and oxcarbazepine are also relatively effective in controlling seizures in this population, suggesting a possible multifocal etiology, which may also explain the high rate of infantile spasms. Our small sample suggests a relative lack of efficacy of vigabatrin and other γ‐aminobutyric acid (GABA)ergic medications, such as typical benzodiazepines, which may be attributable to abnormal GABAergic transmission resulting from the duplication of a cluster of GABAβ3 receptor genes in the 15q11.2‐13 region.